PROSPECTS OF PRODUCTION TECHNOLOGY OF FUNCTIONAL DRINKS FROM FRUITS AND VEGETABLES - Xolmuradov Bobur Bahrom o‘g‘li; Qayumov Beruniy Qudrat o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2023)
The production technology of functional drinks from fruits and vegetables is a promising field with significant potential for growth. This article explores the processing of fruits and vegetables, their use in drinks, and the future prospects of this industry.